Effect of acute intraocular pressure elevation on the minimum rim width in normal, ocular hypertensive and glaucoma eyes. Issue 1 (10th May 2017) - Sharma, Sourabh; Tun, Tin A; Baskaran, Mani; Atalay, Eray; Thakku, Sri Gowtham; Liang, Zhang; Milea, Dan; Strouthidis, Nicholas G; Aung, Tin; Girard, Michael JA
Abstract : Background: To estimate and compare changes in the Bruch's membrane opening—minimum rim width (BMO–MRW) and area in normal, ocular hypertensive and glaucoma eyes following acute elevations in intraocular pressure (IOP). Methods: The optic nerve heads (ONHs) of 104 subjects (31 normals, 20 ocular hypertension (OHT) and 53 with primary glaucoma) were imaged using Spectral-domain optical coherence tomography (OCT; Spectralis, Heidelberg Engineering, Germany). IOP was raised twice by applying a force (0.64 n then 0.9 n) to the anterior sclera using an ophthalmo-dynamometer. After each IOP increment, IOP was held constant, measured with a Tonopen (AVIA applanation tonometer, Reichert, Depew, New York, USA), and ONH was rescanned with OCT. In each OCT volume, BMO–MRW and area were calculated and at each IOP increment. Results: The baseline MRW was significantly smaller in glaucoma subjects (174.3±54.3 µm) compared with normal (287.4±42.2 µm, p<0.001) and OHT subjects (255.4±45.3 µm, p<0.001). MRW of glaucoma subjects was significantly thinner at the first and second IOP elevations than that at baseline (both p<0.01), but no significant change was noted in normal and OHT subjects. There was no significant change of BMO area at acute IOP elevations from baseline in all diagnoses (all p>0.05). Conclusion: Acute IOP elevation leads to compression of the nerve fibre layers of neuroretinal rim in glaucoma subjects only without changing ONH size. This suggests that the neural and connective tissues at ONH level in glaucoma subjects are more susceptible to acute IOP episodes than OHT or normal controls.